Artigo Original: A toxicological evaluation of hepatocytes exposed to the synthetic resorcinolic lipid 3-Heptyl-3,4,6-trimethoxy-3H-isobenzofuran-1-one. PECIBES, 18-23, 2017. - Sarah Alves Auharek; Adilson Beatriz; Bruna Moretto Moreira; Dênis Pires de Lima; Alisson Meza; Roberto da Silva Gomes; Stephanie Dynczuki Navarro; Douglas Santos Monteiro; Rodrigo Juliano Oliveira (Perspectivas Experimentais e Clínicas, Inovações Biomédicas e Educação em Saúde (PECIBES), 2017)
Recent studies showed that resorcinolic lipid 3-Heptyl-3,4,6-trimethoxy-3H-isobenzofuran-1-one (AMS 35AA) may be an important chemotherapy adjuvant, that is not genotoxic nor mutagenic. It is noteworthy that, when AMS35AA is associated with cyclophosphamide, it increases the mutagenic damage, splenic phagocytosis, neutropenia, and induces apoptosis in liver and kidneys. Taken this into account, the present study performed an accurate morphometric investigation of the consequences of the association between AMS35AA and cyclophosphamide on the hepatocytes morphology of Swiss mice. Our results provide strong evidence that the AMS35AA is not toxic and does not induce cellular hyperplasia or hypertrophy in the hepatocytes, which could lead the development of malignant neoplasia. Then, our data support the view that the resorcinolic lipid derivative is not toxic to the hepatocyte, which therefore could have therapeutic applications.